Strategi Branding dan Digital PR dalam Memperkenalkan Batik Sebagai Fashion Modern Kepada Gen-Z (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the influence of modern branding strategies and digital public relations on brand awareness and brand image of batik as a modern fashion among Generation Z and their impact on purchase intention. This study used a quantitative approach with a survey method through an online questionnaire. The research respondents were 125 Generation Z individuals aged 13–28 years in Indonesia who were familiar with modern batik products. The data obtained were analyzed using the Patrial Least Squares-Structural Equation Modeling method. The results showed that modern branding strategies and digital public relations had a positive and significant effect on brand awareness and brand image. Furthermore, brand awareness and brand image were proven to significantly increase purchase intention. Fashion involvement was shown to moderate the relationship between brand image and purchase intention, but did not moderate the relationship between brand awareness and purchase intention. The findings of this study provide theorectial contributions and practical implications for the development of batik marketing strategies.